Teaching of Individual Extension method and Communication - Sanusi, Nassarawa Isma'il; Abdullah, Nassarawa Sanusi (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
The objectives of Extension Education are educational in nature. The effort of the change agent is to change the knowledge, skill and attitudes of the farmers so that their personality undergoes change. This changed ‘man’ is expected to make use of modern advances in Science for solving the problems surrounding him. It is therefore, necessary to understand the teaching and learning processes in extension education. This will enable both to make use of the individual approach fruitful. In this study, the concept of extension education, its importance, scope, purpose and objectives are disclosed. However, the extension teaching and communication were also highlighted; most especially the use of mass media in extension like the radio, interview, audio cassettes, films, television and video as well as printed media in extension education were employed. More so, farm visits and other individual methods like telephone calls and informal contacts were also discussed in brief. The methodology of this work is based on classification of extension teaching method. Lastly, some check list questions were provided in (A) and (B), so as to enable the teacher/learner to know what is been expected in the teaching/learning of an individual extension method via communication. Keywords: Extension Education, Extension Teaching/Learning, Individual extension method, Extension Communication, Farm Visits.